PHYSICAL-MECHANICAL CHARACTERIZATION OF THE WOOD OF Plathymenia reticulata BENTH (VINEYARD-OF-FIELD) NATIVE SPECIES OF THE CERRADO OF THE STATE OF TOCANTINS - Marchesan, Raquel; Souza, Lucas Alves Ferreira; Fortes, Rodrigo Araújo; Reinaldo, Raydel Lorenzo; Barros, André Orathes do Rego; Santos, André Ferreira dos (Floresta, 2020)
Physical-Mechanical Characterization of the Wood of Plathymenia reticulata Benth (Vinhático-do-campo) Species of the Cerrado Biome of the State of Tocantins. The objective of this work was to determine the physical and mechanical properties of Plathymenia reticulata Benth (vinhático-do-campo) wood to indicate its potential use. The wood used in the production of the specimens came from the municipality of Dueré – TO native forest. The basic density, wood retractability, and anisotropy coefficient were obtained from physical tests, and the values of axial compression and static flexion resistance from the mechanical tests. The values obtained showed that the Plathymenia reticulata Benth wood fits the C40 resistance classification for hardwoods, determined by the Brazilian Standard (NBR7190). The average value of the basic density found was 0.64 g cm-3, classified as a medium density wood and the values of tangential, radial and volumetric retractability were 6.11%, 3.06%, 9.39 %, respectively. As for its mechanical characteristics, it presented average values of compressive strength parallel to the fibers, resistance to static flexion, and elastic modulus equal to 58.8MPa, 128.2 MPa, and 12760.0MPa, respectively. The vinhático-do-campo wood can be classified as stable wood and its physical characteristics suggest a normal quality. The species can be applied in light and heavy construction.